Resultado do uso da face ortotópica ou da face invertida do saco herniário sobre o reforço à bassini, na herniorrafia inguinal - Antonio Goulart Monteiro (2014)
Introduction: The proposal of using the herniary sac on strengthening the transversal fascia in inguinal hernia repair, in 1971, resulted in several successful and published works. The orthotopic face or reverse side of the sac used in reinforcing the inguinal triangle was random. Objective:To evaluate which side of the face used, orthotopic or inverted sac, has a better outcome after added on strengthening the Bassini, using the variable infection, rejection and recurrence. Method: From December 2011 to January 2013, a number of 114 operations of direct and indirect inguinal hernia were performed in 99 patients. They were divided into three groups: group A, the Bassini repair (51 operations); group B, orthotopic more Bassini repair (35 operations); and group C, Bassini repair more inverted (28 operations). The statistical test used was Fisher's exact test to compare the results. The follow-up period was performed with returns in 10 days, one month, three months, six months and one year. The following variables were evaluated: wound infection, rejection and recurrence. Ultrasound examination on the operated region of all patients operated on later than six months and one year postoperatively was asked to check the thickness at the site of placement of the screen. Hematoxylin-eosin histology (HE) biopsy of the herniary sac was performed to verify the existence of smooth muscle. The cost of the surgery was evaluated to compare with use of polypropylene mesh. Results: There were six recurrences in group A (11.7%), three recurrences in group B (8.5%) and two in group C (7.1%) (p = 0.850) with no statistical difference. When the inguinal hernias were stratified and only the unilateral indirect inguinal hernia was evaluated, one recurrence was obtained in 18 patients in group A (5%), one in 20 in group B (4%) and none in 16 patients in group C (p = 0.76). Conclusion: All three operations were successful in indirect inguinal hernias, but the repair with the inverted hernia sac showed better results.